2011
DOI: 10.1007/s00425-011-1487-8
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic soybean plants overexpressing O-acetylserine sulfhydrylase accumulate enhanced levels of cysteine and Bowman–Birk protease inhibitor in seeds

Abstract: Soybeans provide an excellent source of protein in animal feed. Soybean protein quality can be enhanced by increasing the concentration of sulfur-containing amino acids. Previous attempts to increase the concentration of sulfur-containing amino acids through the expression of heterologous proteins have met with limited success. Here, we report a successful strategy to increase the cysteine content of soybean seed through the overexpression of a key sulfur assimilatory enzyme. We have generated several transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 54 publications
1
47
0
1
Order By: Relevance
“…Soybean has a fully sequenced genome (Schmutz et al 2010) and results from soybean studies may be translated to other legumes due to extensive synteny (Bordat et al 2011;Lucas et al 2011;McClean et al 2010;Severin et al 2011). Soybean seed has approximately 40% protein in commercial cultivars (Kim et al 2012). However, soybean protein has an unbalanced amino acid composition for monogastric diets with respect to the sulfur (S)-containing amino acids cysteine (Cys) and methionine (Met) (Kim et al 2012;Panthee et al 2006a, b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soybean has a fully sequenced genome (Schmutz et al 2010) and results from soybean studies may be translated to other legumes due to extensive synteny (Bordat et al 2011;Lucas et al 2011;McClean et al 2010;Severin et al 2011). Soybean seed has approximately 40% protein in commercial cultivars (Kim et al 2012). However, soybean protein has an unbalanced amino acid composition for monogastric diets with respect to the sulfur (S)-containing amino acids cysteine (Cys) and methionine (Met) (Kim et al 2012;Panthee et al 2006a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean seed has approximately 40% protein in commercial cultivars (Kim et al 2012). However, soybean protein has an unbalanced amino acid composition for monogastric diets with respect to the sulfur (S)-containing amino acids cysteine (Cys) and methionine (Met) (Kim et al 2012;Panthee et al 2006a, b). Methionine is an essential amino acid, whereas cysteine is considered semi-essential, because farm animals and humans can convert methionine to cysteine (Kim et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical synthesis of cysteine is carried out by the enzyme O-acetylserinesulfhydrylase (OASS). In an attempt to increase sulfur containing amino acids in soybean, Kim et al, overexpressed cytosolic OASS and found that transgenic seeds contained elevated levels of both protein bound cysteine (58-74%) and free cysteine (22-32%) [55]. Another approach used to increase sulfur amino acid content in soybean is the use of a maize zein gene which gives rise to several species of insoluble proteins containing high levels of methionine.…”
Section: Dietary Amino Acidsmentioning
confidence: 99%
“…The sulfur assimilatory pathway in soybean metabolism can be metabolized into molecules that protect plants against oxidative stress. The genetic manipulation of the cytosolic isoform of O-acetylserine sulfhydrylase (OASS), an enzyme involved in the sulfur assimilatory pathway, resulted in high levels of thiols and increased tolerance of plants to metal toxicity [44].…”
Section: Plant Stressmentioning
confidence: 99%